2014
DOI: 10.3390/molecules191118632
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol: Anti-Obesity Mechanisms of Action

Abstract: Abstract:Resveratrol is a non-flavonoid polyphenol which belongs to the stilbenes group and is produced naturally in several plants in response to injury or fungal attack. Resveratrol has been recently reported as preventing obesity. The present review aims to compile the evidence concerning the potential mechanisms of action which underlie the anti-obesity effects of resveratrol, obtained either in cultured cells lines and animal models. Published studies demonstrate that resveratrol has an anti-adipogenic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
123
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(136 citation statements)
references
References 81 publications
4
123
2
1
Order By: Relevance
“…Contrarily, in a recent study using Zucker diabetic fatty (ZDF) rats, it was demonstrated that resveratrol treatment (200 mg/Kg BW/day) did not affect adipose tissue mass or body weight, but resveratrol induced marked changes in the adipose tissue metabolism, such as increased mitochondrial biogenesis with increase in peroxisome proliferator-activated receptor coactivator-1 (PGC-1α) and also increased adiponectin synthesis in a depot-specific manner [27]. Another possible mechanism associated with reduced fat mass induced by resveratrol would be through the increase in fatty acid oxidation in skeletal muscle and liver, increasing energy expenditure and possibly increasing the demand of lipolysis [28].…”
Section: Discussionmentioning
confidence: 98%
“…Contrarily, in a recent study using Zucker diabetic fatty (ZDF) rats, it was demonstrated that resveratrol treatment (200 mg/Kg BW/day) did not affect adipose tissue mass or body weight, but resveratrol induced marked changes in the adipose tissue metabolism, such as increased mitochondrial biogenesis with increase in peroxisome proliferator-activated receptor coactivator-1 (PGC-1α) and also increased adiponectin synthesis in a depot-specific manner [27]. Another possible mechanism associated with reduced fat mass induced by resveratrol would be through the increase in fatty acid oxidation in skeletal muscle and liver, increasing energy expenditure and possibly increasing the demand of lipolysis [28].…”
Section: Discussionmentioning
confidence: 98%
“…Finally, hydroxytyrosol and resveratrol are two phenolic phytochemicals abundant in extra-virgin olive oil and grapes and red wine, respectively. For these two compounds, beneficial effects on metabolic health have been demonstrated, including an anti-obesity action in animals (Cao et al 2014;Aguirre et al 2014) which has been related to interactions with adipogenesis and adipocyte lipid and energy metabolism (Hao et al 2010;Drira and Sakamoto 2014;Mercader et al 2011;Gomez-Zorita et al 2013) among other mechanisms. The dietary interventions chosen thus represent a broad range of treatments shown to attenuate or prevent the development of HFDinduced obesity and associated features of the metabolic syndrome in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Hori dela eta, proposatu da konposatu fenolikoak obesitatearen aurkako molekula bezala erabil litezkeela [20]. Hala ere, gaurdaino argitaratu diren lan gehienak animalietan egin direnez, oso handiak dira lortutako emaitzak gizakietara estrapolatzeko mugak.…”
Section: Konposatu Fenolikoen Efektuak Obesitatean Intsulinarekiko Eunclassified